Shared values of meromorphic functions on a compact Riemann surface. Issue 6 (3rd June 2022) - Ding, Zhiguo; Zieve, Michael E.
Abstract : We prove a new bound on the number of shared values of distinct meromorphic functions on a compact Riemann surface, explain a mistake in a previous paper on this topic, and give a survey of related questions.